INFLUENCE OF HORMONAL AND NON - HORMONAL THERAPIES ON FERTILITY AND SERUM MINERALS PROFILE OF CONCEIVING AND NON-CONCEIVING ANOESTRUS BUFFALOES - Butani, M G; Dhami, A J; Ramani, V P; Savalia , F P; Patel , M D (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A Study was carried out during breeding season on 47 anoestrus / suboestrus buffaloes to evaluate the therapeutic efficacy of hormonal and non-hormonal drugs in inducing fertile oestrus and its influence on serum macro-micro minerals profile. Fifteen true anoestrus buffaloes each were treated either with GnRH (Receptal 5.0 ml) i/m once (Gr-I) or Tono-Prepaline-Cyclomin-Lugols (TPCL) 4 times 4-5 days apart (Gr-II), while 10 suboestrus buffaloes were treated with PGF2α (Juramate 2.0 ml) i/m once (Gr-III), keeping 7 animals as untreated control (Gr-IV). The oestrus induction response and conception rate at induced oestrus in 4 groups were 86.66 & 38.46, 80.00 & 50.00, 100.00 & 40.00, and 42.85 and 66.66 %, respectively, with the oestrus induction interval of 21.50±4.59, 27.73±4.62, 3.62±0.46 and 67.50±14.49 days. The overall serum mineral profile for hormonal and non-hormonal treated anoestrus buffaloes averaged: calcium 9.47±0.15 mg/dl, phosphorus 9.66±0.14 mg/dl and magnesium 3.48±0.09 mEq/L, respectively. The values of zinc, iron, copper, cobalt and manganese were 1.85±0.09, 3.54±0.09, 0.90±0.02, 0.16±0.01 and 0.13±0.01 ppm, respectively. The serum calcium level was significantly higher in all treatment groups as compared to control group. Inorganic phosphorus was significantly higher (P<0.01) in PGF2α treated buffaloes as compared to GnRH treated and control group. The zinc content in PGF2α treated group was significantly lower as compared to GnRH treated group. The values of iron for all treatment groups were significantly higher than the control. The copper and cobalt in GnRH and TPCL treated groups were significantly (P<0.05) higher as compared to control and PGF2á treated groups. The conceived and non-conceived status did not influence significantly the serum profile of these elements in anoestrus buffaloes, though the values were higher in conceived buffaloes.